Effect of Wire Electrical Discharge Machining (WEDM) parameters and additive treatment on surface roughness and dimensional stability of tool steel - Chew, Seow Lee (2013)
The research study presented in this paper is to evaluate the wire electrical discharge machining process parameters; the pulse-on time and wire speed and the options of additive treatment on the work-piece after the conventional hardening process with subzero treatment on dimensional stability and surface roughness. The interaction among the input factors also do investigated to determine if there is significant pattern observed. A series of experiments have been performed on XW 42 cold work tool steel plate with the dimensions of 65mm x 130mm with thicknesses of 10 mm. The test specimens have machined by using different pulse-on time, wire speed and the options of sub-zero treatment by the NEEM Technology Series W-CUT-C-10 WEDM machine. A full factorial Design of Experiments procedure was used in this study. This experiment was based on two level of study with two replicates. The ANOVA analysis was undertaken to determine the significant input factors that affecting the output responses. SOLID Video Measuring Machine was used to measure the diameters of the WEDM output and Surface Roughness Tester was used to measure its surface roughness. Experimental equipments used in this research study have undergone the measurement system analysis to ensure all the data taken are reliable and within the specified confidence level required. The experiment results revealed that input factor pulse-on time has posted significance effect on the surface roughness and dimensional stability of XW 42 tool steel, whereas input factor wire speed shown to have no significance effect on these two output responses. Experiment results also revealed that sub-zero treatment have significance effect on the dimensional stability of the XW 42 tool steel but there was no significance effect on the surface roughness of this tool steel.